Development of Data Acquisition and Control Software for Neutron Radiography Facility at Serpong, Indonesia - Bharoto Bharoto (Atom Indonesia, 2013)
A system for data acquisition and control software for the neutron radiography facility at Serpong has been developed. The software was developed to replace the previously existing control software which was no longer used due to problems on its computer hardware. Visual Basic running under Microsoft Windows operating system was used in developing the new software. In the hardware side, the film grabber and the motor driver were replaced. In the new system, the film grabber which was used to capture the image in the old system is replaced with a programmable CCD camera. The motor driver which was used to control the camera in two directions has been replaced with a four-direction motor driver. The software is capable of displaying the images in a real time mode and record the images in the hard disk of a personal computer. To obtain optimal image quality, the software processes the captured images by performing temperature adjustment, camera exposure time adjustment, and integration of the captured image in a certain frame numbers. The software is capable of taking a number of snapshots at a certain time interval. For neutron tomography purposes, the software takes the snapshots automatically at a sample position in line with the stepping movement of the rotating sample table. The snapshots were saved in a picture format and a numeric format for further processing. The software has been successfully tested for real time method and tomography reconstruction. The data captured by using this software has been verified using both commercial and in-house computed tomography software. Received: 16 January 2013; Revised: 20 August 2013; Accepted: 23 August 2013